Integrated Analysis of mRNA- and miRNA-Seq in the Ovary of Rare Minnow Gobiocypris rarus in Response to 17α-Methyltestosterone - Liu, Shaozhen; Yang, Qiong; Chen, Yue; Liu, Qing; Wang, Weiwei; Song, Jing; Zheng, Yao; Liu, Wenzhong (Frontiers in Genetics, 2021)
17α-methyltestosterone (MT) is a synthetic androgen. The objective of this study were to explore the effects of exogenous MT on the growth and gonadal development of female rare minnow Gobiocypris rarus. Female G. rarus groups were exposed to 25-100 ng/L of MT for 7 days. After exposure for 7 d, total weight and body length were significantly decreased in the 50 ng/L MT groups. The major oocytes in the ovaries of the control group were vitellogenic oocytes (Voc) and cortical alveolus stage oocytes (Coc). In the MT exposure groups, some fish had mature ovaries with a relatively lower proportion of mature oocytes, and the diameter of the Pocs was decreased compared to those of the control group. Ovarian VTG, FSH, LH, 11-KT, E2 and T were significantly increased after exposure to 50 ng/L MT for 7 d. 73449 unigenes, 24 known mature miRNAs, and 897 novel miRNAs in the gonads of G. rarus were found using high-throughput sequencing. Six mature miRNAs (miR-19, miR-183, miR-203, miR-204, miR-205, and miR-96) as well as 6 differentially expressed genes (fabp3, mfap4, abca1, foxo3, tgfb1, and zfp36l1) that may be associated with ovarian development and innate immune response were assayed using qPCR. Furthermore, the miR-183 cluster and miR-203 were differentially expressed in MT-exposed ovaries of the different G. rarus groups. This study provides some information about the role of miRNA-mRNA pairs in the regulation of ovarian development and innate immune system, which will facilitate future studies of the miRNA-RNA-associated regulation of teleost reproduction.